2012
DOI: 10.1103/physrevlett.109.022501
|View full text |Cite
|
Sign up to set email alerts
|

N=16Spherical Shell Closure inO24

Abstract: The unbound excited states of the neutron drip-line isotope 24 O have been investigated via the 24 O(p,p ) 23 O+n reaction in inverse kinematics at a beam energy of 62 MeV/nucleon. The decay energy spectrum of 24 O * was reconstructed from the momenta of 23 O and the neutron. The spinparity of the first excited state, observed at Ex = 4.65 ± 0.14 MeV, was determined to be J π = 2 + from the angular distribution of the cross section. Higher-lying states were also observed. The quadrupole transition parameter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(59 citation statements)
references
References 38 publications
2
57
0
Order By: Relevance
“…First predicted by Goldansky in 1960 [4], two-proton radioactivity has been observed in 45 Fe [5], and genuine threebody decays along with their angular correlations have been observed in many two-proton unbound systems, e.g. 19 Mg, 16 Ne [6] and 6 Be [7]. Analogously, two-neutron unbound systems and their three-body correlations have been measured in several neutron-rich nuclei including 5 O [14], with the last one showing potential for two-neutron radioactivity [15,16].…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…First predicted by Goldansky in 1960 [4], two-proton radioactivity has been observed in 45 Fe [5], and genuine threebody decays along with their angular correlations have been observed in many two-proton unbound systems, e.g. 19 Mg, 16 Ne [6] and 6 Be [7]. Analogously, two-neutron unbound systems and their three-body correlations have been measured in several neutron-rich nuclei including 5 O [14], with the last one showing potential for two-neutron radioactivity [15,16].…”
mentioning
confidence: 94%
“…So far, there has been no correlation measurement of a state decaying by sequential emission of two neutrons, although evidence for sequential decay has been reported for the high-energy continuum of 14 Be [12]. The structure of 24 O, the heaviest bound isotope for which the neutron drip-line is established [17], has been well studied and there is substantial evidence for the appearance of a new magic number N = 16 [18][19][20][21][22]. Two unbound resonances have been observed in 24 O above the one-neutron separation energy [19,23,24], and there is also evidence for resonances above the two-neutron separation energy [19,23] around 7.5 MeV.…”
mentioning
confidence: 99%
“…These studies have revealed that far away from the line of β stability traditional closed-shell numbers may vanish, while others can emerge [1]. For example, neutron shell quenching occurs around N = 20 [2][3][4][5] and N = 28 [6,7], while neutron numbers N = 16 and N = 32 and 34 have been found to feature doubly closed-shell signatures for 24 O and 52,54 Ca [8][9][10][11]. It has been shown that the creation and disappearance of magic numbers are mutually connected [12], raising the question of their respective region of validity.…”
Section: Introductionmentioning
confidence: 99%
“…Another striking feature in the oxygen isotopic chain is the doubly magic nature of 22 O and 24 O [6][7][8][9][10][11] in strong contrast to the lighter elements, where the drip line is marked by nuclei exhibiting a loosely bound halo structure. The neutron-rich oxygen isotopes also provide interesting insights, when viewed coming from their stable isotones.…”
Section: Introductionmentioning
confidence: 99%